The Continental Archipelago of Norilsk - Dahlin, Johanna (Karib – Nordic Journal for Caribbean Studies, 2021)
Russian author Alexander Solzhenitsyn made famous the image of the Soviet prison system Gulag as an archipelago. In this paper, Solzhenitsyn’s idea of the Gulag archipelago is juxtaposed with French Caribbean writer and philosopher Édouard Glissant’s notion of archipelagic thinking. The focus is on the mining city Norilsk in Northern Siberia, one of the “islands” in this penal geography, a city that was largely built using forced labour. It is a long way from the Caribbean to Siberia, but both archipelagos (real and conceptual) share a history that can be termed colonial. While the system that created this penal archipelago of the Gulag was, in Glissant’s terms, a manifestation of thoroughly continental thinking, complete with grand, universalizing tendencies, it may also be possible to sense the diversity and interconnectedness that he attributed to the archipelago. The case of Norilsk is examined through the 2017 documentary A Moon of Nickel and Ice by Canadian film-maker Françoise Jacob. Glissant’s ideas are used to open up and pose questions, rather than to provide definitive answers.